메타졸아마이드 복용에 의한 Stevens-Johnson Syndrome 3례 - 박용주; Yong Ju Park; 문정일; Jung Il Moon; 박찬기; Chan Kee Park (Daihan angwa haghoi jabji, 1999)
최근 메타졸아마이드 복용에 의한 Stevens-Johnson syndrome의 발생이 보고되고 있으며 인종간 특이성 특히 일본인과 한국인에 국한된 발생 가능서이 제시된 바, 우리나라에서의 발생 가능성에 대해 알아보고자 하였다.가톨릭대학교 의과대학 부속병원 안과에서 녹내장 치료를 받던 중 피부에 발진이 생긴 3명의 환자를 대상으로 그 원인을 조사하였다. 3명의 환자는 모두 안압하강을 위하여 메타졸아마이드를 하루 50mg 이상씩 2주 이상 복용하고 있었으며 녹내장 이외의 전신질환이나 다른 약물에 의한 관민반응의 과겨력은 없없다. 피부소견은 수포성 발진이 전신 특히 구강 등 점막에 심하게 나타났으며, 정도의 발열과 무력감 등 전신증상이 동반되었고 약물투여의 중단과 부신피질 호르몬제의 투여 후 별다른 합병증을 남기지 않고 호전되었다. 상기환자들은 메타졸아마이드 이외에 별다른 약물을 쓰지 않았으며 약물의 중단 이후 증상이 호전되었고 피부발진의 양상으로 보아 메타졸아마이드에 의한 Stevens-Johnson syndrome이 발병하였는지에 대한 확진과 인종간 특이성을 알아보기 위해선 보단 많은 증례의 체계적인 연구가 필요할 것이다(한안지 40:613~619, 1999). There have been recent reports on the increasing number of Stevens-Johnson syndrome cases resulting from methazolamide and its relatively higher incidence in Japanese and Korean than any other people. The objective of this study is to examine its developement potential in Korean people. We observed three patients as the subjects of this research, who had been suffering from skin eruption during glaucoma treatment in the Department of Ophthalmology Catholic University, College of Medicine. All of them, for lowering IOP, took methazolamide 50mg a day for more than two weeks, but they had no history of systemic disease but glaucoma or hypersensitivity induced by other edications. With regard to their skin, vesicular eruption came out in their whole body and particularly oral mucosa severely. Also, systemic symptom such as slight fever and general malaise was accompained . However, by quitting the use of methazolamide and medicating corticosteriods instead, they recovered with no serious complication. It can be concluded, therefore, that they had Stevens-Johnson syndrome mainly by methazolamide based on the condition of their skin eruptionand the fact that they got well again by stopping the use of methazolamide on which they chiefly relied. However, a further systematic research on more cases os required with a view to elucidating confirmatory diagnosis and ethnic pecularity of the syndrome(J Korean Ophthalmol Soc 40:613~619, 1999)